PENERAPAN SISTEM INFORMASI AKUNTANSI (KOMPUTERISASI KEGIATAN PERTANAHAN) TERHADAP KUALITAS LAYANAN PUBLIK DI KANTOR PERTANAHAN XYZ - Fanani, Sifa Fauziah; Jannah, Binti Shofiatul (Cahaya Ilmu Bangsa, 2024)
This study aims to determine the application of accounting information systems (computerization of defense activities) to the quality of public services at the XYZ Land Office. The data collection method was carried out by interviewing several staff at the XYZ Land Office and several service users of the XYZ Land Office. The results showed that the implementation of the CTF system has had a positive impact in improving the efficiency and effectiveness of land services, especially in terms of data recording and information management, although there are still some technical obstacles such as occasional system disruptions. Although the level of public satisfaction with land services shows quite good results, there are still challenges in terms of service efficiency, especially when there is an increase in the volume of service requests. Keywords: Public Services; Accounting Information System; Computerization of Land Activities